Kajian Faktor Motivasi Belajar Mahasiswa dalam Peralihan Masa Pandemi Covid-19 Ke Masa Endemi - Grace K. L. Langi (Peneliti.net, 2022)
Motivation to face the demands of the world of education since the last few years for online learning has been formed. However, as the pandemic period will shift to an endemic period, motivation is still needed to support the needs of students in re-reading online learning during an endemic period. The purpose of this scientific work is to identify student learning motivation in the transition from the COVID-19 pandemic to the endemic period. This type of research uses the type of literature study research. This research will be used in an effort to find and collect data, compile, use and interpret existing data. To describe completely, regularly and thoroughly an object of research, namely to describe and explain the concept of student learning motivation in the transition from the COVID-19 pandemic to the endemic period. The result of this scientific work is how strong an individual's motivation will determine the quality of the behavior he displays, both in the context of studying, working and in other life. Learning motivation has an effect on lecturer competence, learning achievement, and e-learning methods given to students. The conclusion is that motivation can help students in actualizing the material presented during the endemic period.